„Welcome homeless, but dear brothers”. Polish military camps in Hungary during World War II - Łochowska, Barbara (City and War, 2021)
After the Soviet aggression against Poland in September 1939, the area of the Kingdom of Hungary became the destination for the evacuation of many Polish soldiers. In 1939, despite the cooperation between Hungary and the Third Reich, the citizens of this country made a great effort to help Poles. In the fall of 1939, over 45 000 Polish soldiers were deployed in approximately 140 camps. Most of the camps were established in urban and rural centers, which significantly influenced the appearance as well as the organizational and population structure of towns and villages. Considering the number of civilian refugees, such a large group of the Polish population was a real challenge for the Hungarian authorities in terms of relocating Poles and taking care of them.The issues raised in the article concern the organization of Polish camps for interned soldiers in the Kingdom of Hungary. It describes the impact of the existence of these centers on the functioning of towns and villages, the population living in them, as well as on Poles themselves, from the perspective of whom staying in Hungary was supposed to be a temporary solution.